Penurunan Kadar Chemical Oxygen Demand (COD) pada Limbah Cair Industri Tahu Menggunakan Arang Aktif dari Pelepah Kelapa Sawit (Elaeis guenensis Jacq.) : Reducing Chemical Oxygen Demand (COD) Levels in Tofu Industrial Liquid Waste Using Activated Charcoal from Palm Oil (Elaeis guenensis Jacq.) Mid-ribs - Khairuddin; Ruslan Ruslan; Muh.Ricky Arisandi M. Tahili; Dwi Juli Puspitasari; Indriani; Husain Sosidi; Prismawiryanti; Moh. Mirzan (KOVALEN: Jurnal Riset Kimia, 2022)
Oil palm midribs (Elaeis guenensis Jacq.) are one of the wastes from oil palm plantations. The high carbon element composition in the palm midribs has the potential to be used as charcoal or activated carbon. Activated carbon can reduce COD levels in tofu industrial wastewater. This study aims to determine the effect of activated carbon mass and contact time on decreasing COD levels in tofu industrial wastewater. Palm midrib charcoal was activated using HCl 1N with the independent variable of activated charcoal mass (1, 3, 5, 7, and 9 grams) and contact times (30, 60, 90, 120, and 150 minutes), while the dependent variable was the percentage decrease COD levels. Activated charcoal from the palm midribs was in accordance with SNI 06-3730-1995 concerning the Quality Standard of Activated Charcoal. The effect of the adsorbent mass showed that the mass increase in activated charcoal was directly proportional to the percentage decrease in COD levels in the tofu industrial wastewater, while the optimum contact time of activated charcoal was obtained at 60 minutes with a decrease in COD levels of 82.13%.